Multicriteria identification of parameters in microscale heat transfer. Issue 3 (6th March 2017) - Kus, Waclaw; Dziatkiewicz, Jolanta
Abstract : Purpose: The purpose of this paper is to present the multicriteria identification method used for solving the microscale heat transfer problem. The thin film exposed to ultrashort laser pulse is modeled using the finite difference method. The parameters of the model are tuned on the basis of experimental data. The multicriteria identification of the numerical model parameters is performed for subsets of experimental data. Design/methodology/approach: The multicriteria identification method is used in the paper. The Pareto front for two criterions is created. The two-temperature model of heat transfer in microscale is used in the numerical model. Findings: The multicriteria identification for two subsets of experimental data leads to different results. The obtained Pareto front allows to choose the most suitable set of numerical model parameters. Originality/value: The multicriteria identification method was used for the first time to solve the microscale heat transfer problem.